2018
DOI: 10.1002/aic.16184
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the effects of multiphase dynamics in catalytic upgrading of biomass pyrolysis vapor

Abstract: A recurring challenge among the variety of existing biomass-to-biofuel conversion technologies is the need to ensure optimal and homogeneous contact between the various phases involved. The formulation of robust design rules from an empirical standpoint alone remains difficult due to the wide range of granular flow regimes coexisting within a given reactor. In this work, a volume-filtered Eulerian-Lagrangian framework is employed that solves chemically reacting flows in the presence of catalytic particles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…These simulations included all the relevant physics: fluid flow, heat transfer, mass transfer, and catalytic reactions in a coupled manner. The assessment studies showed that the VAPM model predictions agree with the fully resolved monolith simulations, and provide (10 ) 3 reduction in CPU time and (10 ) 2 reduction in memory. Along with a significant decrease in the computational cost, the VAPM model allows simple mesh generation and easier convergence of the numerical solution to this multiphysics, multiscale, and multiphase problem.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These simulations included all the relevant physics: fluid flow, heat transfer, mass transfer, and catalytic reactions in a coupled manner. The assessment studies showed that the VAPM model predictions agree with the fully resolved monolith simulations, and provide (10 ) 3 reduction in CPU time and (10 ) 2 reduction in memory. Along with a significant decrease in the computational cost, the VAPM model allows simple mesh generation and easier convergence of the numerical solution to this multiphysics, multiscale, and multiphase problem.…”
Section: Discussionmentioning
confidence: 71%
“…All the cases considered in this work meet the above criterion, with the value of the LHS being (10 ) 2 . Moreover, the above criterion is satisfied for monolith reactors with Reynolds numbers up to (10 ) 2 . With the assumption of local thermal equilibrium, the volume-averaged energy conservation is given by…”
Section: Mass Conservationmentioning
confidence: 92%
See 1 more Smart Citation
“…Terms 1 and 6 are scalar fluxes, which are unclosed and traditionally modelled by classical gradient diffusion models (e.g., the Boussinesq approximation). While these methods are successful in single-phase flows, they have been shown to fall short of being predictive in the context of highly anisotropic, multi-phase flows (Goyal et al, 2018). Finally, the interphase heat exchange terms (Terms 1-5), are the same across the fluid and particle phase descriptions, with the exception of a constant factor of ρ f /(ρ p χ) that appears in the particle phase equation and a factor of ε p / ε f in the fluid phase.…”
Section: One-dimensional Heat Equationsmentioning
confidence: 99%
“…Models for the biomass thermochemical conversion range from detailed but computationally expensive computational fluid dynamics (CFD) simulations 3 to computationally fast ideal reactors. 4 The CFD simulations are necessary to understand the coupling between the reactor flow dynamics and chemical processes.…”
Section: Introductionmentioning
confidence: 99%